The microbiota and helminths: sharing the same niche in the human host. Issue 10 (September 2014) - GLENDINNING, LAURA; NAUSCH, NORMAN; FREE, ANDREW; TAYLOR, DAVID W.; MUTAPI, FRANCISCA
SUMMARY Human gastrointestinal bacteria often share their environment with parasitic worms, allowing physical and physiological interaction between the two groups. Such associations have the potential to affect host health as well as the bacterial and helminth populations. Although still in its early stages, research on the interaction between the microbiome and parasitic helminths in humans offers the potential to improve health by manipulating the microbiome. Previously, supplementation with various nutritional compounds has been found to increase the abundance of potentially beneficial gut commensal bacteria. Thus, nutritional microbiome manipulation to produce an environment which may decrease malnutrition associated with helminth infection and/or aid host recovery from disease is conceivable. This review discusses the influence of the gut microbiota and helminths on host nutrition and immunity and the subsequent effects on the human host's overall health. It also discusses changes occurring in the microbiota upon helminth infections and the underlying mechanisms leading to these changes. There are still significant knowledge gaps which need to be filled before meaningful progress can be made in translating knowledge from studying the human gut microbiome into therapeutic strategies. Ultimately this review aims to discuss our current knowledge as well as highlight areas requiring further investigation.